The Lived Experience of Caregiving and Perception of Service Provision among Family-Caregivers of People with Late-Stage Parkinson's: A Qualitative Study. (3rd February 2023) - Read, Joy; Cable, Sarah; Bartl, Gergely; Löfqvist, Charlotte; Iwarsson, Susanne; Schrag, Anette
Abstract : Background . The complex nature of late-stage Parkinson's requires multiagency support and leads to an increased burden on family members who assume a multiplicity of responsibilities. The aim of this study is to further understand the lived experiences of family-caregivers and their perception of, and satisfaction with, service provision. Methods . This qualitative substudy was a part of the European multicentre Care of Late-Stage Parkinsonism (CLaSP) project. Purposive sampling resulted in a sample of eleven family-caregivers of people with late-stage Parkinson's, who were interviewed using semistructured open-ended questions. Thematic analysis followed. Findings . Three overarching themes were developed from the data: ensuring continuous support is vital to providing care at home, perceiving unmet service provision needs, and advocating and co-ordinating all aspects of care take their toll. These themes include not only experience of services that caregivers find supportive in order to deliver care but also of disjointed care between multiple agencies, a perceived lack of Parkinson's expertise, and there was a lack of anticipatory future planning. The constancy and scope of the family-caregiver role is described, including the need to project manage multiple aspects of care with multiple agencies, to be an advocate, and to assume new roles such as managing finances. Multiple losses were reported, which in part was mitigated by gaining expertise through information and support from professionals and organised and informal support. Conclusion. The intricacies and consequences of the family-caregivers' role and their experience of service provision indicate the need to acknowledge and consider their role and needs, fully involve them in consultations and provide information and joined-up support to improve their well-being, and ensure their continuous significant contribution to the ongoing care of the person with Parkinson's.